Ação gastroprotetora do extrato etanólico de Leonurus sibiricus L. (LAMIACEAE) em camundongos - Biano, Laíza Santos (2021)
Gastric ulcer is considered a common gastrointestinal disease, but it can lead to serious complications and even death, being characterized by lesions in the gastric mucosa. Its clinical and epidemiological characteristics highlight this disease as a public health problem, which treatment is relatively expensive. Natural compounds represent a feasible alternative to fight this disease and the population uses several medicinal plants in the treatment of gastric ulcers, which shows the potential of preparations obtained from these plants. Leonurus sibiricus L. (Lamiaceae) is known as “rubim” or motherwort and is popularly used for various purposes, including stomach disorders. Its anti-inflammatory, antinociceptive and antioxidant activities have been described in the literature. The present study aimed to evaluate the action of the ethanol extract of the aerial parts of Leonurus sibiricus L. (EELs) on the gastric mucosa of mice submitted to models of gastric injury and pylorus ligation. After approval by the Animal Research Ethics Committee at UFS (under number 03/18), the acidified ethanol- induced ulcer model (60% ethanol/ HCl at 0.3 mol/L) was used to evaluate the effect of EELs (50, 100 and 300 mg/kg, p.o.). In this model, the concentration of sulfhydryl compounds and lipid peroxidation in the gastric mucosa were also evaluated. The participation of non-protein sulfhydryl compounds (NP-SH), nitric oxide (NO), prostaglandins (PG), ATP-sensitive K+ channels (KATP) and hydrogen sulfide (H2S) in the gastroprotective effect of EELs (300 mg/kg) was investigated in this ulcer model. The effect of EELs (300 mg/kg) on gastric volume, acidity and pH as well as the mucus in the gastric content were evaluated in the pylorus ligation model. Pre-treatment with EELs, at 300 mg/kg, but not at 50 and 100 mg/kg, reduced the relative area of gastric injury induced by acidified ethanol (p<0.01), compared to the vehicle group. The administration of EELs reduced lipid peroxidation (p<0.05 and p<0.01 respectively to 50 and 300 mg/kg) and increased the sulfhydryl content (p<0.05 and p<0.01 respectively to 100 and 300 mg/kg) in the stomach when compared to the vehicle group. Pre-treatment with the NP-SH blocker (N-ethylmaleimide, 10 mg/kg, i.p.) or a KATP blocker (glibenclamide, 10 mg/kg, i.p.) inhibited the gastroprotective response caused by EELs (300 mg/kg; p<0.001), but it did not occur with pre-treatments with an inhibitor of prostaglandin synthesis (indomethacin, 10 mg/kg), NO (L-NAME, 70 mg/kg) or H2S (DL-Propargilglycin, 10 mg/kg). EELs (300 mg/kg) reduced the volume of acid secretion after pylorus ligation, but did not affect acidity or pH, unlike cimetidine, which significantly altered all parameters. In addition, treatment with EELs increased gastric mucus production (300 mg/kg; p<0.001). These results provide evidence that EELs exert gastroprotective action in mice by reducing oxidative stress and with the participation of NP-SH and KATP channels.